Understanding Customer Satisfaction Feedback in an IT Outsourcing Company: A Case Study on the Insigma Hengtian Company - XIA, Xin (Institutional Knowledge at Singapore Management University, 2015)
To reduce budget and improve competitive power, some companies would outsource their information technology (IT) functions to a third-party company referred to as an IT outsourcing company. After an outsourcing company completes a project, it would collect feedback from the customer. Analyzing this feedback could help to further improve the service of the outsourcing company. To our best knowledge, there are limited studies on customer satisfaction feedback. In this paper, we perform a case study of customer satisfaction feedback in an IT outsourcing company. We analyze 3 years of customer satisfaction feedback reports in Insigma Hengtian, which is the one of the well-known IT outsourcing companies in China with more than 2,000 employees. Each report specifies the overall satisfaction of a customer, and feedback on factors that contribute to customer satisfaction including: business knowledge and technical skills, work attitude, communication skills, on-time delivery, cost-effectiveness, etc. In total, we investigate 8 factors which are related to customer satisfaction. Next, we build a logistic regression model and analyze the statistical significance and collinearity characteristics of the independent factors used to build the model. We find that among the 8 factors, business knowledge and technical skills, on-time delivery, and cost-effectiveness are the 3 most important factors, and all of them have positive impact to customer satisfaction.